2004
DOI: 10.1159/000079167
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Interleukin-10-Producing T Cells in the Peripheral Blood of Severe Unstable Atopic Asthmatics

Abstract: Background: Although IL-10 is known as an immunoregulatory cytokine produced by various cells including T cells, its basic profile in atopic asthma remains uncertain. Objective: The profiles of IL-10 production in circulating CD4+ T cells of atopic asthmatics were investigated with respect to clinical severity. Methods: Forty atopic asthmatics were divided into three groups: mild, and severe but stable and severe unstable asthmatics. Eosinophils were counted in the peripheral blood and sputum, and exhaled nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 73 publications
0
25
1
Order By: Relevance
“…The role of IL-10 producing T-cells in the severity of allergic asthma in adults has been studied by MATSUMOTO et al [100] by comparing mild, severe-stable and severe-unstable asthmatics.…”
Section: T-regulatory Cells and Asthmamentioning
confidence: 99%
“…The role of IL-10 producing T-cells in the severity of allergic asthma in adults has been studied by MATSUMOTO et al [100] by comparing mild, severe-stable and severe-unstable asthmatics.…”
Section: T-regulatory Cells and Asthmamentioning
confidence: 99%
“…This suggests that IL-10 production from T-cells is unregulated in asthmatic cases. Since IL-10 promoters polymorphisms have been reported (17), it is possible that IL-10 effector functions are reduced in atopic asthmatic subjects, in which a decrease in IL-10 expression in asthma has been reported (18). It has also been proved that remission of allergy symptoms is related to an increase in IL-10 expression in allergen-specific T-lymphocytes (19).…”
Section: Discussion:-mentioning
confidence: 99%
“…Our previous study showed that IL-10+CD4+ T cells in the peripheral blood of atopic asthmatics was decreased in severe unstable asthmatics compared with mild and severe stable asthmatics [21]. Another study reported that the production of IL-10 in monocytes was also impaired in cases of severe asthma [25].…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of IL-10-producing CD3+, CD4+ and CD8+ cells in the peripheral blood were significantly higher in atopic asthmatics than in healthy subjects [20]. In addition, we reported that IL-10+CD4+ T cells in the peripheral blood were decreased in severe unstable asthmatics compared with mild and severe stable asthmatics [21]. Although these results suggest a possible association of peripheral blood IL-10+CD4+ T cells with atopic asthma, several questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%